Interleukin-6 and IgA-rheumatoid factor are crucial for baseline erosiveness, and anti-citrullinated peptide antibodies for radiographic progression in early rheumatoid arthritis treated according to a treat-to-target strategy. (3rd September 2018) - Fedele, AL; Petricca, L; Tolusso, B; Alivernini, S; Canestri, S; Di Mario, C; Bosello, SL; Ferraccioli, G; Gremese, E
Abstract : Objectives : To define baseline clinical and immunological characteristics [anti-citrullinated peptide antibodies (ACPAs), immunoglobulin M (IgM)- and IgA-rheumatoid factor (RF), and interleukin-6 (IL-6) levels] involved in determining baseline erosiveness, outcome, and radiographic progression among seropositive and seronegative early rheumatoid arthritis (ERA) patients. Method : The 408 ERA patients enrolled in the study were monitored every 3 months according to the treat-to-target strategy. At baseline and after 12 months, hand and foot radiographs were evaluated using the Sharp/van der Heijde erosion score. Results : At diagnosis, seronegative patients were older and had higher Disease Activity Scores (DASs) than seropositive patients. A higher risk of erosiveness at baseline was conferred by IgA-RF positivity and IL-6 plasma levels ≥7.6 pg/mL, particularly when simultaneously present. In multivariate analysis, disease duration and IL-6 plasma levels ≥7.6 pg/mL arose as independent variables associated with presence of erosions at onset. Radiographic progression at 1 year follow-up, which occurred in 11.1% of ERA patients, was predicted by ACPA positivity, together with higher age at diagnosis. Despite similar percentages of good European League Against Rheumatism response, DAS and Boolean remission being observed over time among seropositive and seronegative patients and between erosive and non-erosive subjects, ERA patients who were erosive at onset, IgA-RF seropositive, and simultaneously having high baseline IL-6 plasma levels (≥7.6 pg/mL) were treated to a greater extent with tumour necrosis factor blockers after 12 months. Conclusion : IgA-RF positivity and IL-6 plasma levels are crucial for baseline erosiveness, while ACPA positivity represents the strongest risk factor for developing radiographic progression in ERA.